Customer Relationship Management (CRM) as a Life Style - Al-Homery, Hussein A.; Asharai, Hasbullah; Ahmad, Azizah (Pakistan Journal of Humanities and Social Sciences, 2018)
This article is about the concept of CRM life style. It is an intellectual concept, where the researcher analyses the abbreviation “CRM” by returning each letter to its origin to prove the hypothesis of the concept. Where the researcher proposes the CRM database structure for the CRM process as a customer life style, where it depends on the business workflow process and the specialty of each business, and where the database structure tried in our case study for an authorized automobile dealer in Riyadh, Saudi Arabia.